Cooperative problem solving with personal mobile information tools in hospitals - Buchauer, Anke; Werner, Roland; Haux, Reinhold (Methods of information in medicine, 1998)
Health-care professionals have a broad range of needs for information and cooperation while working at different points of care (e.g., outpatient departments, wards, and functional units such as operating theaters). Patient-related data and medical knowledge have to be widely available to support high-quality patient care. Furthermore, due to the increased specialization of health-care professionals, efficient collaboration is required. Personal mobile information tools have a considerable potential to realize almost ubiquitous information and collaborative support. They enable to unite the functionality of conventional tools such as paper forms, dictating machines, and pagers into one tool. Moreover, they can extend the support already provided by clinical workstations. An approach is described for the integration of mobile information tools with heterogeneous hospital information systems. This approach includes identification of functions which should be provided on mobile tools. Major functions are the presentation of medical records and reports, electronic mailing to support interpersonal communication, and the provision of editors for structured clinical documentation. To realize those functions on mobile tools, we propose a document-based client-server architecture that enables mobile information tools to interoperate with existing computer-based application systems. Open application systems and powerful, partially wireless, hospital-wide networks are the prerequisites for the introduction of mobile information tools.
Elektronische Reproduktion der Druck-Ausgabe 7. Februar 2018
Gesehen am 05.08.2025